Monitoring Spatial Conditions and Road Traffic of the Tsunami Evacuation Route in Padang City Using Geographic Information System (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
The traffic of the tsunami evacuation route is an essential aspect of disaster mitigation. This relates to minimizing the possibility of fatalities and property damage as well as preparing communities to be resilient to disasters. This also refers to the accessibility of a body of water as measured by its length, type, and position along the coast. There are numerous roads that serve as evacuation routes for the earthquake and tsunami disasters in the present day, but their conditions are lacking. Furthermore, there has been no detailed research on the monitoring of the tsunami evacuation route in Padang City. Moreover, Padang City is extremely vulnerable to earthquakes and tsunamis based on its past and its possibility of future natural disasters. This research used a quantitative survey with scoring and analysis of Open Route Services (ORS) tools in the QGIS application. The results indicated that the road accessibility for cars was in priority 1 with a score of 28,02%, meanwhile the accessibility for motorbikes and pedestrian was in priority 1 with a score of100%. Therefore, it is not optimal for two vehicles to share the same road channel simultaneously. The tsunami-safe zone is located in the relatively elevated eastern area of Padang City. This study also identified and recommended which sections of the road must be enhanced for the tsunami evacuation route in priority 1.